Mechanism of mitotic recombination: insights from C. elegans. (December 2021) - Belan, Ondrej; Anand, Roopesh; Boulton, Simon J
Abstract : Homologous recombination (HR) plays a critical role in largely error-free repair of mitotic and meiotic DNA double-strand breaks (DSBs). DSBs are one of the most deleterious DNA lesions, which are repaired by non-homologous end joining (NHEJ), homologous recombination (HR) or, if compromised, micro-homology mediated end joining (MMEJ). If left unrepaired, DSBs can lead to cell death or if repaired incorrectly can result in chromosome rearrangements that drive cancer development. Here, we describe recent advances in the field of mitotic HR made using Caenorhabditis elegans roundworm, as a model system.